Ultrafast energy transfer from perovskite quantum dots to chromophore - Chaochao Qin; Jie Li; Jian Song; Shuhong Ma; Jicai Zhang; Guangrui Jia; Zhaoyong Jiao; Zunlue Zhu; Yuhai Jiang; Zhongpo Zhou (Results in Physics, 2023)
Energy transfer plays an essential role in inorganic semiconductor nanocrystal-chromophore hybrids which show potential applications in light collection and emitting. The understanding of the fundamental mechanics of energy transfer processes is vital to enhance the performance of light-harvesting optoelectronic devices. Here we report the effect of varying donor sizes on energy transfer from perovskite nanocrystals to chromophore molecules. Both single energy transfer and triplet transfer mechanisms have been identified to occur between CsPbBr3 quantum dots linked to a Rhodamine B dye. The ease of adjusting optical properties via particle-size controlling provides a particular platform to accommodate excited-state couplings in perovskite-chromophore hybrids.